Tasks for a theoretical psychology of emotion. Issue 2 (17th February 2022) - Reisenzein, Rainer
ABSTRACT: In the first part of the article, the central role of theory in emotion psychology is underscored and reasons are given why more theoretical psychology of emotion is needed. In the second part, nine tasks for the theoretical psychology of emotion are defined, by refining and extending three of the general tasks of theoretical psychology proposed 70 years ago by Sigmund Koch [Theoretical psychology, 1950: An overview. Psychological Review, 58 (4), 295. https://doi.org/10.1037/h0055768 ]. The nine tasks are: (1) Analysis, rational reconstruction and critique of existing emotion theories. (2) Comparison of different theories. (3) Systematization and integration of theories. (4) Reconstruction of the development of theories over time. (5) Analysis, reconstruction and critique of theory-data and data-theory inferences. (6) Analysis, reconstruction and critique of the complete set of arguments for and against specific emotion-theoretic assumption and whole theories. (7) Analysis, reconstruction and critique of measurement theories for emotions. (8) Development of new emotion theories and theories of emotion measurement. (9) Information about theoretical and methodological developments of interest to emotion psychology in other subdisciplines of psychology and in neighbouring sciences, and export of theories and methods to other disciplines.